2022
DOI: 10.1096/fj.202201157rr
|View full text |Cite|
|
Sign up to set email alerts
|

Targeting SARS‐CoV‐2 by synthetic dual‐acting thiol compounds that inhibit Spike/ACE2 interaction and viral protein production

Abstract: The SARS‐CoV‐2 life cycle is strictly dependent on the environmental redox state that influences both virus entry and replication. A reducing environment impairs the binding of the spike protein (S) to the angiotensin‐converting enzyme 2 receptor (ACE2), while a highly oxidizing environment is thought to favor S interaction with ACE2. Moreover, SARS‐CoV‐2 interferes with redox homeostasis in infected cells to promote the oxidative folding of its own proteins. Here we demonstrate that synthetic low molecular we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…In conclusion, we report, for the first time, decreased NRF2 and HO1 levels and an inverse correlation with ISGs in RSV-infected, hospitalized children that shows higher disease severity than HRV-infected patients, thus, suggesting the contribution of NRF2 dysregulation to the severity of such viral infections. Interestingly, it has been reported that NRF2-activating molecules are able to inhibit inflammatory responses and the replication of respiratory viruses [29,43]. Our findings are consistent with the hypothesis that NRF2 antioxidant response may be effective as a critical control mechanism in reducing production of IFN-stimulated genes during RSV infections in the upper respiratory tract, and suggest the possible use of NRF2 activators to counteract viral replication and ameliorate the clinical course in RSV-infected children.…”
Section: Discussionsupporting
confidence: 91%
“…In conclusion, we report, for the first time, decreased NRF2 and HO1 levels and an inverse correlation with ISGs in RSV-infected, hospitalized children that shows higher disease severity than HRV-infected patients, thus, suggesting the contribution of NRF2 dysregulation to the severity of such viral infections. Interestingly, it has been reported that NRF2-activating molecules are able to inhibit inflammatory responses and the replication of respiratory viruses [29,43]. Our findings are consistent with the hypothesis that NRF2 antioxidant response may be effective as a critical control mechanism in reducing production of IFN-stimulated genes during RSV infections in the upper respiratory tract, and suggest the possible use of NRF2 activators to counteract viral replication and ameliorate the clinical course in RSV-infected children.…”
Section: Discussionsupporting
confidence: 91%
“…Therefore, GSH levels in HUVEC were evaluated using HPLC at different time points (1, 4, and 8 h), as reported in [ 56 ]. GSH content decreased markedly after 1 h in anoxia and a similar profile was detected after 4 h. Only at 8 h were the cells able to restore their baseline levels, probably thanks to the activation of their antioxidant defense systems, as illustrated in Figure 5 .…”
Section: Resultsmentioning
confidence: 99%
“…25% (v/v) Na 2 HPO 4 0.3 M and 10% (v/v) DTNB were added to the supernatants for thiol determination by HPLC through a BDS Hypersil™ C18 column (5 μm, 150 × 4.6 mm; Thermo Scientific). Separation and elution conditions were previously described elsewhere 34,35 . Following the detection at 330 nm, quantitative measurements were compared with known concentration standards and normalized to the protein content.…”
Section: Methodsmentioning
confidence: 99%
“…Separation and elution conditions were previously described elsewhere. 34,35 Following the detection at 330 nm, quantitative measurements were compared with known concentration standards and normalized to the protein content.…”
Section: Glutathione and Thiol Group Detectionmentioning
confidence: 99%